Pengertian, Dampak, dan Solusi Bagi Pelaku LGBT - Nasution, Mustafa; Darania Anisa (Rahis Cendekia Indonesia, 2024)
LGBT stands for lesbian, gay, bisexual and transgender. They are a collection of sexual deviant behaviors and gender identities that are seen as contrary to nature and reject the provisions of God Almighty. At first, sexual orientation and gender identity were often considered taboo and recognized as a form of deviation. However, human rights movements, activism, and increased public awareness have driven greater acceptance. Since the 1960s, resistance to stigma and discrimination has begun to emerge, especially with events such as the Stonewall Rebellion in New York in 1969, which is often considered a turning point for the LGBT movement. Since then, various countries have passed laws supporting LGBT rights, including same-sex marriage and protections against discrimination. So, many people have supported and accepted this behavior. It needs to be reviewed and revisited, because this behavior is still very contrary to norms, culture, and religion. So that if someone falls into this, many negative impacts will occur in him